Improving Kayang's Learning Outcomes Through Training Methods in Class V Students of SD Negeri 38, Ambon City - Rina Gaite; Johanna Matitaputty (International Journal of Education, Information Technology, and Others, 2023)
This research is a Classroom Action Research (CAR). This research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The research subjects were fifth grade students at SD Negeri 38 Ambon City, totaling 18 students. The data sources were teachers, students and researchers.Data collection techniques are by observation, tests, and documentation or archives. Based on the results of the analysis obtained a significant increase from cycle I to cycle I and cycle II. This can be seen from the student learning outcomes in the pre-cycle of the number of students 18 only 10 students who completed and 8 students did not complete or with a percentage of 75% of students completed and 25% of students did not complete. Then the learning outcomes shown by students in cycle I showed an increase, namely 10 students or 75% were included in the complete category and the remaining 8 students or 25% were in the incomplete category. In cycle II the increase in student learning outcomes is 100% or 10 students are in the complete category. The conclusion from this study is that using the training method can be used to improve learning outcomes in javelin throwing in class V students at SD Negeri 38 Ambon City